Real Option Analysis (ROA) - Armanto Witjaksono (The Winners, 2003)
Net Present Value (NPV) method have populer since middle 70’s and now most of expert felt that method has several limitation, especially if used to analyse big scale investment alocation capital. Another method that begin to popular is Real Option Analysis (ROA) that use to replace Net Present Value (NPV) method. The strenght of Real Option Analysis (ROA) method is the flexiblelity in giving information for the decision maker. The weakness of Real Option Analysis (ROA) method is the simple mathematic formula, as the formula in NPV method, is not found yet.